2016
DOI: 10.1016/j.pop.2016.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Bipolar Disorder

Abstract: Bipolar disorder is a chronic mental health disorder that is frequently encountered in primary care. Many patients with depression may actually have bipolar disorder. The management of bipolar disorder requires proper diagnosis and awareness or referral for appropriate pharmacologic therapy. Patients with bipolar disorder require primary care management for comorbidities such as cardiovascular and metabolic disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 20 publications
0
20
0
2
Order By: Relevance
“…First, the study employed a data mining procedure to attain a large sample size (4,191 HS patients, with 5 controls per patient) from a previously authenticated database containing medical information on the majority of Israel's population [20]. Previous studies assessing the association between bipolar disorders and medical comorbidities have focused primarily on physical conditions such as cardiovascular disease, diabetes, chronic obstructive pulmonary disease, or pneumonia [40,41], while less attention has been given to the comorbidity of this disorder with dermatological conditions. This study stresses the importance of investigating these associations to facilitate the diagnosis of such co-occurrence.…”
Section: Discussionmentioning
confidence: 99%
“…First, the study employed a data mining procedure to attain a large sample size (4,191 HS patients, with 5 controls per patient) from a previously authenticated database containing medical information on the majority of Israel's population [20]. Previous studies assessing the association between bipolar disorders and medical comorbidities have focused primarily on physical conditions such as cardiovascular disease, diabetes, chronic obstructive pulmonary disease, or pneumonia [40,41], while less attention has been given to the comorbidity of this disorder with dermatological conditions. This study stresses the importance of investigating these associations to facilitate the diagnosis of such co-occurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Bipolar disorder (BD) is a common, complex, and severe mood disorder with progressive social and cognitive function disturbances . BD is characterized by the presence of mania or hypomania, and episodes of depression.…”
Section: Introductionmentioning
confidence: 99%
“…The gold standard used in the treatment of BD is lithium (Li), which is a mood stabilizer approved by the Food and Drug Administration (FDA) . Previous studies have shown that Li is effective in acute manic episodes, and reduces the risk of manic and depressive relapses …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations